2019
DOI: 10.2147/ott.s192373
|View full text |Cite
|
Sign up to set email alerts
|

<p>Retrospective study of the efficacy and toxicity of lobaplatin in combined chemotherapy for metastatic breast cancer</p>

Abstract: Objective To study the efficacy and adverse reactions of lobaplatin combined with other chemotherapy drugs in the treatment of metastatic breast cancer. Methods This retrospective analysis enrolled 114 patients who were diagnosed with advanced breast cancer from January 2010 to December 2015. Lobaplatin and another chemotherapeutic agent were given to patients. The efficacy and side effects were evaluated after at least two cycles of chemotherapy. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In the course of clinical treatment, it is always accompanied by certain side-effects, such as autotoxicity, bone marrow suppression, nephrotoxicity and alopecia. To further explore more effective therapy for RB, the present study investigated the third-generation platinum derivative lobaplatin, a novel chemotherapeutic drug, that has exhibited potent antitumor activity with fewer side-effects than carboplatin in non-small-cell lung and metastatic breast cancer (27,28). In addition, the present study compared the therapeutic effects with a two-sided inequality test and concluded that lobaplatin exhibited lower cytotoxicity and exerted more prominent therapeutic effects than carboplatin on RB cells in vitro and in mice in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In the course of clinical treatment, it is always accompanied by certain side-effects, such as autotoxicity, bone marrow suppression, nephrotoxicity and alopecia. To further explore more effective therapy for RB, the present study investigated the third-generation platinum derivative lobaplatin, a novel chemotherapeutic drug, that has exhibited potent antitumor activity with fewer side-effects than carboplatin in non-small-cell lung and metastatic breast cancer (27,28). In addition, the present study compared the therapeutic effects with a two-sided inequality test and concluded that lobaplatin exhibited lower cytotoxicity and exerted more prominent therapeutic effects than carboplatin on RB cells in vitro and in mice in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lobaplatin is commonly used for transcatheter arterial chemoembolization because its pH is close to the normal physiological pH of the human body. [9][10][11][12] The development of these three generations of platinum drugs has shown that platinum drugs are widely used as essential drugs for the treatment of common malignancies. Most conventional platinum nanoparticles use their own antioxidant effect for anti-tumor therapy, or even more, they use external energy to generate active oxygen-like species that can inhibit the growth of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Lobaplatin (LBP) is a third-generation platinum antitumor drug, which is clinically used for the treatment of chronic metastatic breast cancer, myelogenous leukemia, and small cell lung cancer in China . It has been reported that lobaplatin suppressed cancer metastasis and developed antitumor activity by arresting cell cycle progression to inhibit cancer cell proliferation and induce cancer cell apoptosis. LBP is usually administered intravenously because of its good solubility, but the rapid hydrolysis of the drug in vivo would generate varying degrees of side effects, such as gastrointestinal toxicity, nephrotoxicity, myelosuppression, and thrombocytopenia, which largely restrict the clinical applications. It will be seen that improving the stability of platinum-based anticancer agents in the gastrointestinal fluid is the primary issue for making them into an oral formulation, and it is expected to reduce toxicity . Therefore, it is worthwhile to further develop a new form of platinum-based anticancer agent with high stability in gastrointestinal fluid, high efficiency, and reduced toxicity.…”
Section: Introductionmentioning
confidence: 99%